Present Situation of the Citrus Tristeza Virus in the Valencian Community - Cambra, Mariano; Serra-Aracil, José; Villalba, David; Moreno, Pedro (IOCV, 2021)
Tristeza disease of citrus (CTV) occurred heavily in the Ribera Alta areas of the Jucar Valley (Valencia) beginning in 1957. From that time an estimated 10 million trees grafted on sour orange have been killed. Most of them were in the Valencian Community (VC), which is composed of Alicante, Castellon, and Valencia, where about 160,000 ha (approximately 64 million trees) are planted. Only 20% of these trees are grafted on tolerant rootstocks. To determine the real incidence of CTV, an infection map was made by random sampling 0.1% of the trees in Alicante (15,705), Castellon (15,915) and Valericia (33,000). Diagnosis of CTV was done by ELISA-DAS using CTV-specific monoclonal antibodies. The selection of sampling fields was randomized and proportional to the citrus areas on aerial photographs. Three young shoots, about 10-15 cm long, were collected from each tree. The sample collection method, their transport to the laboratory, and analysis were standardized and the field data, together with the final diagnosis were included in a computerized databank. Preliminary data from 80% of the samples indicate that 8.5% of the hectarage does not appear to be diseased; that on 60.4% the incidence of infected trees is lower than 10%; that on 25.3% the incidence varies from 10% to 50%; and on 5.8% of the total hectarage in the VC, the incidence of infected trees is higher than 50%.